2016
DOI: 10.1136/bmjopen-2015-009775
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of hyponatraemia among elderly patients with heart failure in Uganda

Abstract: BackgroundHyponatraemia is a common electrolyte disturbance among older patients. We determined the prevalence of and factors associated with hyponatraemia among older patients with predominantly acute decompensated heart failure attending a tertiary hospital in Kampala, Uganda.ObjectivesMain study aim: (1) to determine the prevalence of hyponatraemia among patients aged 60 years and above with heart failure attending Mulago National Referral Hospital; (2) to describe the factors associated with hyponatraemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…There is a possibility that metabolic and other effects of thiazide diuretics may vary in specific populations which should be accounted for in future studies. Several studies have linked the use of loop diuretics to hyponatremia [15,33]. Loop diuretics promote natriuresis and water loss through the inhibition of sodium chloride reabsorption at the ascending limb of Henle's loop [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a possibility that metabolic and other effects of thiazide diuretics may vary in specific populations which should be accounted for in future studies. Several studies have linked the use of loop diuretics to hyponatremia [15,33]. Loop diuretics promote natriuresis and water loss through the inhibition of sodium chloride reabsorption at the ascending limb of Henle's loop [17].…”
Section: Discussionmentioning
confidence: 99%
“…This therapy is prescribed to patients with chronic renal failure [ 14 ], arterial hypertension [ 14 ], cirrhosis [ 6 ], and especially to those with symptomatic heart failure (HF) [ 9 ]. Thiazides, loop diuretics, and potassium sparing diuretics induce water and salt excretion [ 12 , 14 , 15 ] and may promote sodium loss through renal effects [ 16 ]. It has been suggested that some diuretic combinations may additionally increase the risk of hyponatremia [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Geriatrics studies in Uganda have mainly focused on: exploring geriatric education needs, knowledge and attitudes of health workers towards geriatric care services (where 69% of them lacked geriatric training and 80% had poor to fair knowledge of geriatric care (12)), the impact of HIV among older adults (20), older persons as caregivers to people infected and affected by HIV/AIDS (21), and loneliness among older adults in Uganda (22). Other studies have focused on: health care access challenges faced by the elderly (23,24), hyponatraemia among older adults (25), and perceptions of anaemia among the older population in Southwest Uganda (26).…”
Section: Geriatrics In the Context Of Uganda's Health Systemmentioning
confidence: 99%
“…With regards to geriatric research, studies have mainly focused on: exploring geriatric education needs, knowledge and attitudes of health workers towards geriatric care services (where 69% lacked geriatric training and 80% had poor to fair knowledge of geriatric care (11)), the impact of HIV among old people (15), older persons as caregivers to people infected and affected by HIV/AIDS (16), and loneliness among the aged in Uganda (17). Other studies have focused on: health care access challenges by the elderly (18,19), hyponatraemia among old patients (20), and perceptions of anaemia among the older population in Southwest Uganda (21). The readiness of Uganda's public health system to provide geriatric friendly care services to its ageing population remains underexplored.…”
Section: Geriatrics In the Context Of Uganda's Health Systemmentioning
confidence: 99%